Lean Manufacturing Approach to Reduce Wastefulness During Production of Train Car-Body Using VALSAT Method - Aria Auliandri, T; Chofiya Alfiani, N (KnE Social Sciences, 2018)
Based on the National Statistics Bureau, the number of train passengers in Indonesia has steadily increased; hence, it has increased demands for train car bodies. Train production in Indonesia is conducted by PT. Train Industry (INKA), Madiun. A manufacturing enterprise that processes raw materials into finished goods through a complicated process before delivering the goods to consumers. During the process, wasteful activities frequently occur and do not add any value stream. Wasteful activities extend and delay the production process, which harms the company. This research was conducted at the Fabrication Division of the train manufacture company, PT. INKA, Madiun. It is aimed to identify and minimize wasteful activities during train car body production process conducted by the Fabrication Division using Lean Manufacturing approach. Analysis on wasteful activities is conducted using Value Stream Mapping with Process Activity Mapping (PAM) and Supply Chain Response Matrix (SCRM) and calculated with VALSAT. Based on the research findings, the most wasteful activity is waiting time. Waiting time is caused by the delay in the arrival of raw materials, which causes further delay in production time, unfit machinery capability and barely-skilled labors. Based on PAM, wasteful activities, which are mostly caused by delays in non-value adding activity (NVA), took up 271.5 hours or 16.80% of total production time. Based on SCRM, total lead time of car body production until it reached the Finishing Division amounted to 131 days. After analysis, suggestions for improvement are given to minimize wasteful activities. Based on the suggestions, a decrease in NVA was achieved at 88.67% rate and lead time decreased by 15.64%. Keywords: lean manufacturing, wastefulness, Value Stream Mapping, VALSAT